Research on the Impact of Sex Ratio of Lamprey on Ecosystem Stability Based on Dynamic System Model - Peng, Runze (Transactions on Computer Science and Intelligent Systems Research, 2024)
In the Great Lakes of the United States, lampreys, as an invasive species, have seriously affected the survival of native fish and destroyed the ecological environment. To find natural ways to control its population, it is necessary to study the relationship between lamprey and other species. The sex ratio of lampreys has an enormous impact on their population size. To study the impact of lampreys on ecosystem, it’s important to investigate the relationship between the sex ratio of lampreys and their population size. Based on Logistic model, Lotka-Volterra model, Competition model and Independence model, a Dynamic System model of simplified ecosystem is established. The effects of lampreys on other species under different interspecific relationships were explored. A population quality assessment model was established, and the population of lampreys was quantitatively assessed from eight aspects including Predation Control, Food Chain Role, Ecosystem Provider, et al.